Disability identity development: A systematic review of the literature - Forber-Pratt, Anjali J; Lyew, Dominique A; Mueller, Carlyn; Samples, Leah B (Rehabilitation psychology, 2017)
The purpose of this systematic review was to synthesize existing empirical research on disability identity development. This review is organized to present the demographics of participants and types of disabilities represented in the existing data, measures of disability identity development and theoretical models of disability identity development. Electronic databases (EBSCO, PsycINFO, ERIC, and Sociological Abstracts) were searched for all peer reviewed empirical studies published between 1980 and 2017. Articles were excluded if they were theoretical and/or did not include participants with disabilities, or focused on a disability-specific community identity rather than general disability identity. Empirical articles (N = 41) were included in the final review. An overwhelming majority (75.6%) were qualitative in nature, with only 22% of the articles reviewed being quantitative and only 1 that utilized a mixed methods design. The results suggest that disability identity can be considered a unique phenomenon that shapes persons' ways of seeing themselves, their bodies, and their way of interacting with the world. Disability identity development has the potential to become an important factor in developing effective interventions and/or therapies. Identity development is a fundamentally social process, and identities are formed through mirroring, modeling, and recognition through available identity resources, and so it is imperative that able-bodied professionals (i.e., rehabilitation professionals, therapists, teachers and caregivers) working with individuals with disabilities become aware of this developmental process to be able to better support individuals along this journey. (PsycINFO Database Record